Dive - Gordon Korman (New York, 2003)
Kaz,Dante, Andriana and Star aren't the best divers in the world.But they've been chosen to spend the summer exploring the depths of the sea. There are only a few problems. First, the sharks. Killer Sharks. And then the fact that the people running the program are covering up something big...and mysterious. These four kids are about to make the discovery of their lives - And put themselves in danger because of it.
Keywords: Realistic Fiction